AI-Driven Augmented Reality Learning Based on Big Data in Islamic History Education: A Transformation Model from Conventional to Visual-Immersive Approaches - Ilham Rosyadi; Retno Widyaningrum (LP3M Pascasarjana STAI Ibnurusyd, 2026)
History teaching in Islamic Education remains dominated by conventional lecture-based approaches that position students as passive recipients of information. This approach reduces learning engagement, limits historical imagination, and does not align with the characteristics of the digital generation, who are accustomed to interactive and visual learning experiences. This study employs a conceptual qualitative approach using a literature review design and theoretical analysis grounded in constructivism, multimedia learning, and experiential learning. Data were collected from books and scholarly articles on Artificial Intelligence (AI), Augmented Reality (AR), Big Data, and digital transformation in education, then analyzed thematically to develop an integrative conceptual model. The findings indicate that AI enables personalized learning through learning analytics, AR provides immersive visualization of historical events, and Big Data supports evidence-based instructional decision-making. These technologies collectively form an AI-Driven Augmented Reality Learning model based on Big Data that transforms history education from a textual and narrative approach into a visual, immersive, adaptive, interactive, and contextual learning experience. The proposed model also redefines teachers as facilitators and designers of technology-enhanced learning while emphasizing the importance of adequate digital infrastructure and digital literacy to ensure effective implementation in Islamic Education.